The Effects of Public Views Inclusivity on the Legislative Process of the Finance Bill, 2024 in the National Assembly of Kenya - Ichwara, Elijah; Kigatiira, Kinya; Ndung’u, Kahura (International Journal of Research in Interdisciplinary Studies, 2025)
The main objective of this study was to examine the role of participatory communication in the legislative process of the Finance Bill, 2024, in the National Assembly of Kenya. Specifically, it sought to investigate the role of facilitators' attributes on the legislative process of the Finance Bill, 2024, in the National Assembly of Kenya, to evaluate the role of public stakeholders’ diversity on the legislative process of the finance Bill 2024 in the National Assembly of Kenya, to assess the role of citizen engagement methods on the legislative process of the Finance Bill, 2024 in the National Assembly of Kenya; to determine the role of public views on the legislative process in the National Assembly of Kenya to examine the moderating role of Political Will and Organizational Capacity on the legislative process of the finance Bill 2024 in the National Assembly of Kenya. The study was guided by participatory communication and deliberative theories and utilized a qualitative research design. The target population of the study consisted of 349 members of the Kenyan parliament. This included 290 members elected from constituencies, 47 women representatives elected from each of the 47 counties, 12 members nominated to represent special interests, and the Speaker. Further, 2,109,284 members of the public who are between the ages of 18 years to 28 years old (Generation Z) were drawn from four counties, namely, Nairobi City, Nakuru, Mombasa, and Kisumu Counties. The study employed both purposive and quota sampling to select respondents from the National Assembly and the public across the four targeted counties, respectively. The sample comprised 20 members of parliament. They included 3 members from the Budget and Appropriation Committee, 3 members from the Finance and Budget Committee, 1 MP from the Speaker’s Panel, 1 Parliamentary Liaison Officer from the Ministry of Finance, and 12 individual MPs and key informants selected based on their active participation in public hearings, stakeholder engagements, and debates on the Finance Bill 2024. Quota sampling was used to select 40 Generation Z respondents (aged 18–28), with 10 participants drawn from each of the four counties. Interviews and focus group discussions (FGDs) were utilized to collect data. Members of parliament were interviewed members of the public who are between 18 years to 28 years were purposively selected and were included in the focus group discussions. The pilot study involved five (5) Senators from the Senate of Kenya and twenty (20) members of the public from Machakos County This study adopted a qualitative data analysis approach, consistent with the research design. Computer-assisted qualitative analysis in NVivo software version 9 helped to analyse relationships and themes of data in content analysis. The influence of moderating variables of political and organizational capacity was also obtained based on regression analysis. Data was presented in form of narrations and verbatims. The results revealed that the Finance Bill 2024 process showed that facilitator impartiality, clarity, and cultural sensitivity improved trust and inclusivity, while stakeholder diversity enriched deliberations but faced structural inequities. Citizen engagement raised awareness but lacked policy impact due to weak feedback loops, political dominance, and institutional capacity gaps, reducing participation to largely symbolic gestures. The study concluded that The Finance Bill 2024 process demonstrated that without neutrality, inclusivity, feedback, and institutional commitment, participatory communication remains symbolic, undermining trust, limiting public influence, and weakening the legitimacy of legislative decision-making in Kenya. The study recommended that future legislative processes should ensure impartial facilitation, inclusive engagement formats, and institutionalized feedback mechanisms. Parliament must strengthen capacity to process submissions, track amendments publicly, and communicate outcomes transparently, ensuring citizen input meaningfully shapes laws.